Niger : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, and Requests for Waiver of Nonobservance of Performance Criteria and Augmentation of Access-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Niger. (IMF Staff Country Reports; Country Report, 2006)
Niger's First Review Under the Poverty Reduction and Growth Facility, and Requests for Waiver of Nonobservance of Performance Criteria and Augmentation of Access are discussed. The sharp rise in food prices pushed up inflation in 2005, while the food shortage affected one-fourth of the population, resulting in malnutrition and the spread of diseases, especially among children. Increased drought-related imports and a significant deterioration in the terms of trade, mainly because of higher oil prices, have weakened Niger's external position.